(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article presents the representation of Muslims in Middle English literature. It is described that is a complex and multifaceted topic, reflecting the cultural, religious, and political dynamics of the medieval period. Moreover, it has been analyzed that the relationship between Christians and Muslims was heavily influenced by the Crusades, trade, and cultural exchanges.